Por uma pedagogia da emotividade na educação matemática : ensino, ética-estética e afetividade - Vargas , Jackson Luís Santos de (2022)
The aim of this thesis is to understand how the possible articulations established between teaching, ethics-aesthetics and effectiveness – perceived, or not, by the regent teachers of the class – can contribute to the mathematics learning of elementary school students. The main theorists who contributed to the foundation were Henri Wallon, Emmanuel Levinas, Jacques Derrida, Nadja Hermann and Paulo Freire. Methodologically, a structured questionnaire was applied, disseminated via the internet in different social networks, with the adhesion of 37 participants. All of them are Elementary School Mathematics teachers, with teaching experience ranging from 1 to 32 years. The analysis of the obtained results was inspired by Lawrence Bardin's Content Analysis. The results lead to a pedagogical situations: continuing education courses that reflect the reality experienced by the social group in which the school is inserted; meetings between professors, which enable integration, critical reflection of their practice, exchange of experiences with other colleagues in the same area and in others; dialogue with the school's management team, as the verticalization of orders and the frequent demands for compliance with the school curriculum make it difficult for the teacher to work, overloading them and, therefore, affecting their emotional state; dialogue with the management team to resolve different conflicts that occurred in the school, whether with students, colleagues, parents, or even with the management team itself. Furthermore, teachers do not realize that, when working on Art in Mathematics classes, including the active participation of students in the elaboration and execution of activities, dialoguing, and working on sensitivity, they allow the student to be positively linked to them and to the discipline. Likewise, they do not realize that impositions, underestimations of the student's ability to learn Mathematics, as well as judgments and classes focused on abstraction, distance and/or negatively link student, teacher, and curricular component, since there is no identification of the student with the developed content. This can make you feel like an outsider inside your own classroom, excluded, unable to continue with that learning. These findings seem to indicate that teachers think they have created positive bonds with students due to technical knowledge, as they consider the discipline of Mathematics difficult and not for everyone. The analysis performed shows that the processes of sensitization in pedagogical practices; the positive links between professors and students resulting from the processes of hospitality, empathy and valuing emotions; the commitment and care for the other in the teacher-student relationship contributes to the mathematics learning of elementary school students, corroborating the thesis that the relationship between teaching, ethics-aesthetics and affectivity, occurred from three relational movements: teaching and ethics-aesthetics; ethics-aesthetics and affectivity; teaching and affectivity make Mathematics learning potentially meaningful. The common point that emerges in the relationship of these three movements, teaching; ethics-aesthetics and affectivity, is the Pedagogy of Emotivity